"THIS MEME IS WHAT WE CALL PROGRESS”: HISTORY-AS-MEME, MEME-AS-HISTORY ON 4CHAN - McEwan, Sean Rutherford (AoIR Selected Papers of Internet Research, 2018)
Memes “act as the locus of memory”, says Gabriella Coleman of the peculiar relationship 4chan has to its own history, made necessary by the ephemeral nature of large amounts of its content (2009). Rather than having an on-site permanent archive as such, its collective history and memory is sublated into and through the circulation and production of memes. Taking this as a prompt, this paper makes the case for the (re)production, circulation, and referencing of memes as embodiment of a particular historical ontology: a mode of being constructed in relationship to, and through, its own past. Memes, in other words, are a new way of thinking about, and experiencing (digital) history: they contribute to, and are part of, new “infra-structures of feeling” (Coleman 2017). With this in mind, I use Benjamin’s reading of Klee’s Angelus Novus as a framing device to start to think about how memes encourage and embody certain modes of being-in-the-world. I do so in specific reference to 4chan and its privileging of a certain subject position along lines raced, classed and gendered, although possibilities for other forms and spaces are considered. On 4chan, the New Man of neofascism remakes the world memetically, in his own image.